Experimental research on water-lubricated marine stern tube bearings in conditions of improper lubrication and cooling causing rapid bush wear. (March 2016) - Litwin, Wojciech; Dymarski, Czesław
Abstract: Water-lubricated polymer bushes are increasingly popular in sliding bearings of marine propellers, water turbines, and pump shafts. This environmentally friendly solution is relatively simple and usually proves to be durable. However, in practical experience one may also observe cases of rapid wear or even malfunctions of this type of bearing, some of which may be caused by insufficient flow of lubricant. The main purpose of the conducted research was to identify how different bearing types operate under conditions of no lubricant flow. The conducted research determined that certain bearings continue to work properly despite a lack of lubricant flow and cooling. This is due to low frictional resistance levels, resulting in sufficiently low heat being generated in the friction zone of such bearings and dispersed into the surroundings once the bearing׳s temperature has risen and stabilized at a safe level. Highlights: Six water lubricated bearings in real-life scale were experimentally tested and compared. Bearings were tested in conditions of limited lubrication and cooling. Conditions during tests were typical for marine bearings and water turbine bearings. Some of the bearings are able to operate despite lack of lubricant flow.